2022
DOI: 10.1101/2022.12.15.520614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soaring migrants flexibly respond to sea-breeze in a migratory bottleneck: using first derivatives to identify behavioural adjustments over time

Abstract: Millions of birds travel every year between Europe and Africa detouring ecological barriers and funnelling through migratory corridors where they face variable weather conditions. Little is known regarding the response of migrating birds to mesoscale meteorological processes during flight. Specifically, sea-breeze has a daily cycle that may directly influence the flight of diurnal migrants. We collected radar tracks of soaring migrants using modified weather radar in Latrun, central Israel, in 7 autumns betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Our GAMM of landing force showed that owls perched more softly the closer they came to the next hunting strike. To identify periods when there was a significant change in landing force, we calculated the first derivative f ′( x ) of the estimated smoothed relationship between the time to the next strike and the peak landing force, according to each perch type, to highlight significant periods of positive or negative relationships(55, 56). Periods of significant change were identified as those time points where the simultaneous confidence interval on the first derivative does not include zero.…”
Section: Methodsmentioning
confidence: 99%
“…Our GAMM of landing force showed that owls perched more softly the closer they came to the next hunting strike. To identify periods when there was a significant change in landing force, we calculated the first derivative f ′( x ) of the estimated smoothed relationship between the time to the next strike and the peak landing force, according to each perch type, to highlight significant periods of positive or negative relationships(55, 56). Periods of significant change were identified as those time points where the simultaneous confidence interval on the first derivative does not include zero.…”
Section: Methodsmentioning
confidence: 99%